2019
DOI: 10.1089/apc.2018.0289
|View full text |Cite
|
Sign up to set email alerts
|

Recent HIV Risk Behavior and Partnership Type Predict HIV Pre-Exposure Prophylaxis Adherence in Men Who Have Sex with Men

Abstract: Men who have sex with men (MSM) reporting higher HIV risk behavior over time are often more adherent to pre-exposure prophylaxis (PrEP), but it is unclear if recent risk behavior and partnership type affect long-term PrEP adherence. HIV-negative MSM and transgender women completing the 48-week randomized study TAPIR (Daily Text Messages to Support Adherence to PrEP in At-Risk for HIV Individuals) were included. At baseline and weeks 24 and 48, a modified Calculated Risk (mCalcR) Score estimated the likelihood … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Our previous work has found that those with higher HIV risk behaviors have better adherence. 25 This could account for some of the somewhat lower adherence seen in this study, but there may be many other contributing factors for transgender individuals to adherence that need to be further analyzed. The MI intervention was delivered through phone by 1 coordinator to all study sites to be cost-effective and to ensure fidelity.…”
Section: Discussionmentioning
confidence: 92%
“…Our previous work has found that those with higher HIV risk behaviors have better adherence. 25 This could account for some of the somewhat lower adherence seen in this study, but there may be many other contributing factors for transgender individuals to adherence that need to be further analyzed. The MI intervention was delivered through phone by 1 coordinator to all study sites to be cost-effective and to ensure fidelity.…”
Section: Discussionmentioning
confidence: 92%
“…Results from each primary study are summarized in Table 1 [ 17 31 ]. Findings from four additional secondary analyses of the Moore et al primary study [ 17 , 18 , 22 , 27 , 28 ] are summarized in Table 1 . Two studies [ 19 , 20 ] (20%) used e-health platforms and focused on patient awareness and acceptability of PrEP, three studies [ 23 , 29 , 31 ] (30%) used telehealth and focused on uptake, adherence and persistence in PrEP, and five studies [ 21 , 24 27 ] (50%) were mHealth primarily focused on adherence to PrEP.…”
Section: Resultsmentioning
confidence: 99%
“…30% reported a decrease in barriers. Participants self-reported mean PrEP adherence rates of 91% through daily entries in the mSMART app Moore et al (2017) [ 27 ] Adherence to PrEP Urban N = 398 Asian = 12 (6.2%); Black = 52 (13.1%); White = 295 (74.1%); Multiple = 24 (6.0%); Other = 7 (1.8%) Hispanic Ethnicity = 119 (29.9%) Cisgender men, transgender women MSM Adults: ≥ 18 years No The text messaging intervention did not significantly improve adequate adherence (≥ 719 fmol/punch) compared to the SOC (72.0% vs 69.2%; p = 0.58), but did improve near-perfect adherence (≥ 1246 fmol/ punch) a secondary outcome, through week 48 (33.5% vs 24.8%, p = 0.06) Secondary analysis studies • Blumenthal et al (2019) [ 17 ]—Analysis found the correlation between self-report measures of adherence were significant associated with quantifiable biomarker collected • Blumenthal et al (2019) [ 18 ]—Study calculated modified calculated risk scores to estimate likelihood of HIV seroconversion based on self -reported risk behaviors. Analysis found participants with moderate or high-risk behaviors had higher PrEP adherence levels compared to lower risk groups • Hoenigl et al (2018) [ 22 ]—No statistical difference was found in PrEP adherence among substance users compared to non substance users • Pasipanodya et al (2018) [ 28 ]—growth mixture modeling to identify 4 trajectories of text-reported adherence.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation